Modelling Supply Chain Management In B2B E-Commerce Systems - Idris Asmuni (Bandar Lampung University (UBL), 2014)
Applying supply chain management in e-commerce systems has been a need for enterprise to win the competition global in a term of customer-oriented market. Although investing in supply chain technology demand high costs and resources, many companies attempt to strengthen business function with systems application under ERP packages and other systems related. This paper discusses about B2B e-commerce modelling as an integral part of E-Business in supply chain company activities. Some critical factors which bring successfull of B2B e-commerce according to previous research also explained that will be valuable information for management in building partnership. With the innovation of information technology, the pattern of partnership in the future will give some new opportunities in improving customer service.